Effects of inosine on reperfusion injury after cardiopulmonary bypass - Veres, Gábor; Radovits, Tamás; Seres, Leila; Horkay, Ferenc; Karck, Matthias; Szabó, Gábor (Journal of cardiothoracic surgery, 2010)
Inosine, a break-down product of adenosine has been recently shown to exert inodilatory and anti-inflammatory properties. Furthermore inosine might be a key substrate of pharmacological post-conditioning. In the present pre-clinical study, we investigated the effects of inosine on cardiac function during reperfusion in an experimental model of cardioplegic arrest and extracorporal circulation.